Prevalence and risk factors for inappropriate birth weight for gestational age - Dittakarn Boriboonhirunsarn (2018)
Background: Infants with an inappropriate birth weight for their gestational age are more likely to develop complications during pregnancy and postpartum, and have increased long-term health risks. Objectives: To determine the prevalence and risk factors for infants with inappropriate birth weight for their gestational age. Methods: We enrolled 820 women with uncomplicated, singleton pregnancies who gave birth to a live born infant at term. Prepregnancy baseline and obstetric information were extracted from medical records, including body mass index (BMI), gestational weight gain, and infant birth weight. Prevalence of small-for-gestational age (SGA) and large-for-gestational age (LGA) infants was determined. We compared variables between groups to identify associated factors. Results: Prevalence of SGA was 2.6% and LGA was 10.5%. Prepregnancy BMI and gestational weight gain were significantly higher in the LGA than in the SGA group (P = 0.041 and < 0.001, respectively). The birth weight and gestational weight gain, but not the prepregnancy BMI, were significantly different (P < 0.001). Logistic regression analysis determined that inadequate gestational weight gain significantly increased the risk of SGA (adjusted OR 3.20, 95%CI 1.06 to 9.64, P = 0.039), and significantly reduced the risk of LGA (adjusted OR 0.43, 95% CI 0.20 to 0.91, P = 0.028). Excessive gestational weight gain significantly increased the risk of LGA (adjusted OR 2.00, 95% CI 1.21 to 3.30, P = 0.006). There was no significant association with prepregnancy BMI. Conclusions: Controlling gestational weight gain may improve maternal and neonatal outcomes.